Merciful Judgments and Contemporary Society Legal Problems, Legal Possibilities - Sarat, Austin (Cambridge Cambridge University Press, 2011)
"Merciful Judgments in Contemporary Society: Legal Problems/Legal Possibilities explores the tension between law's need for and dependence on merciful judgments and suspicions that regularly accompany them. Rather than focusing primarily on definitional questions or the longstanding debate about the moral worth and importance of mercy, this book focuses on mercy as a part of, and problem, for law. Whether one starts from a worry about rules and discretion, about the attitudes of citizens and their leaders, or ways to undo the past, merciful judgments challenge and perplex, just as they help to sustain, our legal system. Charting these possibilities and problems is the work that this book seeks to do. Here we ask what challenges merciful judgments pose for law? When and why do those judgments encourage and nurture legal ingenuity and resourcefulness? When and why do they precipitate crises and breakdowns in legal authority? This book is a product of The University of Alabama School of Law symposia series on "Law, Knowledge & Imagination." This series explores the ways law is known and imagined in a diverse array of disciplines, including political science, history, cultural studies, philosophy, and science. In addition, books produced through the Alabama symposia explore various conjunctions of law, knowledge, and imagination as they play out in debates about theory and policy and speak to venerable questions as well as contemporary issues" -- Provided by publisher.
When can or should legal judgment be merciful? / Austin Sarat -- The place of mercy in legal discourse / Robert A. Ferguson -- Commentary on Chapter 1 : response to "The place of mercy in legal discourse" / Jamie Leonard -- Mercy, crime control, and moral credibility / Paul H. Robinson -- Commentary on Chapter 2 : thoughts on mercy and self-examination / William Brewbaker -- Defending a role for mercy in a criminal justice system / James Staihar and Stephen Macedo -- Commentary on Chapter 3 : commentary on "Defending a role for mercy in a criminal justice system" / Pamela Pierson -- Actions of mercy / Alice Ristroph -- Commentary on Chapter 4 : Reflections on "Actions of mercy" / Steven H. Hobbs -- A Feminist view of mercy, judgment, and the "Exception" in the context of transitional justice / Susan H. Williams -- Commentary on Chapter 5 : the interpretative process : feminist reconstructions / Timothy Hoff.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Criminal justice, Administration of -- Moral and ethical aspects; Law and ethics; Transitional justice